2019
DOI: 10.1007/978-3-030-37670-3_3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring How Component Factors and Their Uncertainty Affect Judgements of Risk in Cyber-Security

Abstract: Subjective judgements from experts provide essential information when assessing and modelling threats in respect to cyber-physical systems. For example, the vulnerability of individual system components can be described using multiple factors, such as complexity, technological maturity, and the availability of tools to aid an attack. Such information is useful for determining attack risk, but much of it is challenging to acquire automatically and instead must be collected through expert assessments. However, m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2
1

Relationship

5
1

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 17 publications
0
14
0
Order By: Relevance
“…Another practical concern remains in demonstrating the efficacy of this approach across a broader variety of real-world contexts-expanding upon a growing body of research (cf. Ellerby et al, 2019aEllerby et al, , 2020Navarro et al, 2016;Wallace et al, 2016). Finally, it is important that future empirical research is conducted to directly compare this interval-valued response mode against existing methods of both lower (e.g., Likert, VAS) and higher complexity (e.g., multi-step interval elicitation, SHELF, FRS)-to establish and quantify the trade-offs between information capture and important practical concerns regarding response efficiency (i.e., workload, survey duration, perceived complexity, training requirements), which have a large influence on likelihood of broader adoption.…”
Section: Summary and Future Workmentioning
confidence: 99%
See 1 more Smart Citation
“…Another practical concern remains in demonstrating the efficacy of this approach across a broader variety of real-world contexts-expanding upon a growing body of research (cf. Ellerby et al, 2019aEllerby et al, , 2020Navarro et al, 2016;Wallace et al, 2016). Finally, it is important that future empirical research is conducted to directly compare this interval-valued response mode against existing methods of both lower (e.g., Likert, VAS) and higher complexity (e.g., multi-step interval elicitation, SHELF, FRS)-to establish and quantify the trade-offs between information capture and important practical concerns regarding response efficiency (i.e., workload, survey duration, perceived complexity, training requirements), which have a large influence on likelihood of broader adoption.…”
Section: Summary and Future Workmentioning
confidence: 99%
“…Recent work by present authors has included development of open-source software for efficient digital administration of interval-valued surveys (DECSYS-c.f. Ellerby, McCulloch, Young & Wagner, 2019), which is available to download via https://www.lucidresearch.org/decsys.html from GitHub. This paper builds upon this-reporting a study designed to provide an initial validation of this approach.…”
Section: Introductionmentioning
confidence: 99%
“…Complementary research studies are ongoing to address socio-technical considerations-concerning the basic efficacy of this response mode to capture multiple sources of respondent uncertainty and response variability-and also to demonstrate the value of the resulting data in real-world contexts [8]. The present study was conducted to demonstrate both the value provided by interval-valued responses and the use of the DECSYS software's ellipse response mode, to capture said intervals.…”
Section: Introductionmentioning
confidence: 99%
“…This study provides evidence that interval elicitation using ellipses is not only effective (cf. [3]- [5]), but efficient. Results found that respondents preferred to give interval rather than point estimates, because they perceived them as no more difficult to provide, while permitting more effective communication of their desired responses.…”
Section: Summary Conclusion and Future Workmentioning
confidence: 99%
“…Despite these, a growing body of complementary theoretical, practical and empirical work has contributed to a recent surge in interest in interval-valued response elicitation. This research has worked to address each of these barriers-ranging from empirical studies to establish efficacy and potential value across a variety of real-world applications [3]- [7], to creation of open-source software tools to facilitate administration at scale [8], to development and evaluation of mathematical and statistical methods to best handle and interpret the richer information that is captured [9]- [17], cf. Fig.…”
Section: Introductionmentioning
confidence: 99%